Today Roland Barthes is Dead: Killing the Body of Theory in The Seventh Function of Language by Laurent Binet - Ostojic, Zvezdana (Recherches sémiotiques / Semiotic Inquiry, 2019)
On February 25th 1980, in front of the Coll ge de France, a traffic accident claimed a victim whose name was not unfamiliar: that of the famous semiotician and literary critic Roland Barthes. Was it merely an accident, or was it murder? In a bizarre police investigation, in which the boundaries between reality and fiction are blurred, police commissioner Jacques Bayard and his assistant, the young semiotician Simon Herzog, will prove that Roland Barthes was indeed killed, because he was in possession of a mysterious manuscript on the seventh function of language.This article demonstrates the strategies that Laurent Binet adopts to problematize the myth that has been formed around the work and life of Roland Barthes. By staging Barthes's fictional murder, Binet liquidates the canonical monument of French Theory via the lowbrow intervention of the detective story. By killing off Roland Barthes, a tutelary figure of modern semiology, Binet questions the limits and potentialities of Barthes's legacy in today's post poststructuralist era when theorists are being increasingly assimilated into the popular culture, while also being fetishized within the closed academic eco-chambers. Binet adopts a popular genre to follow Barthes's steps in dismantling yet another one of the bourgeois myths - the Canon of High Theory. Finally, this article shows that Binet’s novel is an attempt to reanimate Barthes and French Theory by resituating their writings in the realm of the popular, material, and accessible.